Owners and users: an approach to ways of living in northeast Montevideo - Lucía Abbadie (Cidades, Comunidades e Território)
Reflecting on the categories of owners and users and the way these categories have influenced (or not) livelihoods, this paper questions how values affect the planning and implementation of communal living. The focus of this paper is on the ‘value’ of living in certain places, the kinds of appropriations made by those who live there (or not), as well as the organisational processes that are necessary to achieve basic services and then ‘be part’ of the city, beyond the possession of private property. The importance of individual property is linked to a framework of valuation that is supported by public policy, and that permeates most of the actions in contemporary society. Based on the experience of neighbourhood organizations inside informal settlements and housing cooperatives in the northeast of Montevideo, the paper focuses on what issues are important to people. Many of these organisations struggle every single day to ensure a better life for people who live there, trying to improve their quality of life. Interesting experiments in grass-roots solidarity have been carried out to better it, but in many cases, people seem not to care about property ownership.